Role of Glioblastoma Craniotomy Related to Patient Survival: A 10-Year Survey in a Tertiary Care Hospital in Pakistan - Shahid, Saman; Hussain, Kamran (Journal of Neurological Surgery Part B: Skull Base, 2017)
A total of 270 glioblastoma patients were treated for tumor resection during 2004 to 2014. The following variables were examined: patient age group (PAG) and percent of the extent of resection (EOR) in four types of resections: gross total resection (GTR), subtotal resection (STR), partial resection (PR), and biopsy/decompression (BD). The Karnofsky performance scale (KPS) was used and the average survival time noted. The least survival time (7 months) was noticed in the patient age group 18 to 35 years with biopsy only, whereas, the maximum survival time (14.5 months) was noted with the patient age group 54 to 71 years by gross tumor resection. The largest number of (n = 76) patients had PR (80%) and these patients had an average survival time of 10.5 months. Total 190 patients out of 270, with EOR (100–80%) had a KPS score “0” (80 and above) and total 80 patients out of 270 patients, with EOR (50%) had a KPS score “1” (below 80). The correlation was statistically significant at (p < 0.050) for EOR (%) and KPS score (0/1) only. Correlation analysis showed that the maximum resection has a strong impact on the glioblastoma patient's survival. A lesser EOR correlated with poor quality of life and also a decreased survival of patients.
Keywords: glioblastoma; craniotomy; patient survival; extent of resection; quality of life